Análise estatística e comparativa de eventos chuvosos em escala subdiária em bacias hidrográficas do Brasil - Gonçalves, Euler Noiman (2018)
The understanding of rain patterns focusing on the position of the peak in the rainfall event is important to support hydrological studies and the planning of water resources use. In this research, subdaily rainfall data of nine gauges located throughout the Brazilian territory were used. The methodology for rainfall event classification into patterns (left skewed, triangular central, right skewed, rectangular, bimodal and not characterized) was based on studies that suggest the division of the rainfall event into bands. After the classification of rainfall events into patterns, the features of the patterns were statistically. The Minimum Time Intra-event (MIT) criterion was used to the selection the rainfall events. The following MIT's were used 15 and 30 minutes, 1, 2, 3, 6, 12 and 24 hours. Therefore, the aim of this study was to classify and to examine the patterns rainfall events in watersheds located in Brazil. The results indicate that the left skewed type is the most frequent, independently of the used MIT and independently of the gauge location. However, the results demonstrate that the behavior of the hietograms changes with the change of the MIT, as well as, changes the properties of a rainy event, and there is a need for further study in the choice of this methodology.